Influence on the Phase Formation and Strength of Porcelain by Partial Substitution of Fly Ash Compositions - Kutty, Nur Azureen Alwi; Noh, Mohamad Zaky; Mayzan, Mohd Zul Hilmi; Iya, Sani Garba Durumin (International Journal of Engineering and Technology, 2018)
This paper presents the study of the influence on the phase formation and strength of the porcelain by the partial substitution of fly ash. The fly ash was calcined at the temperature of 800 °C and partially substituted into feldspar. Each mixture were mixed and pressed into green pellets sintered at different sintering temperature (1100 – 1300 °C) at the interval of 50 °C for 120 min. The compressive strength, crystalline phase and the microstructure of the porcelain were investigated. The optimum physical and mechanical properties were obtained at 5 wt % of fly ash porcelain sintered at 1250 °C. The apparent porosity reaches a minimum value with 0.22 % which is nearly to zero and obtained the highest compressive strength of 105.40 MPa. The XRD results reveal that the highest percentage of mullite was obtained at the substitution of 5 wt % of fly ash with 49.0 %. The glassy phase shows an increasing trend with dissolution of mullite content which affects the strength and microstructure of the porcelain.